EVALUASI EVALUASI FAKTOR PENENTU PENYELESAIAN PELATIHAN MANDIRI: KAJIAN KOMPARATIF ANTARTIGA TOPIK PELATIHAN - Riswadinata, Indra; Furqon, Mukhammad Nurul; Miati, Siti; Ferdiansyah, Afifudin (Komunitas Manajemen Kompetitif, 2025)
Technology-based self-directed training has become strategic in human resource competency development, yet varying completion rates necessitate in-depth evaluation of factors influencing participant success. This study aims to identify determining factors for successful completion of self-directed training through comparative analysis of three training topics: Body Language, Scientific Poster, and 3-Minute Presentation. Analysis was conducted on 186 participants using multivariate approaches including crosstabulation analysis, Chi-Square test, Principal Component Analysis (PCA), multivariate analysis, and Linear Discriminant Function Analysis. Demographic data showed female dominance (59.7%) and students (94.1%). Chi-Square analysis revealed no significant relationship between training topics and non-completion rates (p > 0.05). PCA identified two main dimensions: Techno pedagogical Infrastructure dominated by stable internet access (loading 0.837), technical skills (0.812), and familiarity with BRIN Learning Management System (BRILIANT) platform (0.790); and Personal Motivation and Suitability with career goal alignment as the strongest predictor (loading 0.863). Multivariate analysis confirmed that success determinants are consistent across all training topics (p > 0.05). Discriminant analysis showed that participants who successfully completed training had more stable internet access, stronger intrinsic motivation, and higher learning autonomy compared to those who did not complete. Self-directed training success is more determined by technological infrastructure, intrinsic motivation, and self-regulation capabilities rather than specific learning material characteristics. These findings support Self-Determination Theory and emphasize the importance of addressing digital divides and developing autonomous motivation to enhance self-directed learning effectiveness